2018
DOI: 10.1515/humo-2017-0030
|View full text |Cite
|
Sign up to set email alerts
|

Underwater dolphin kicks of young swimmers – evaluation of effectiveness based on kinematic analysis

Abstract: Purpose. The aim of the study was to distinguish the kinematic indicators influencing the average horizontal velocity of swimming (v cOM ) with underwater dolphin kicks (UDK). Methods. The study involved 15 boys and 20 girls (mean age, 11.5 ± 1.00 years; height, 1.57 ± 0.09 m; training experience, 2.5 ± 1.00 years) practicing swimming 7 times a week. We determined the body height (H), the length of the body with the arms lifted (L b ), and the best result in the 50-m freestyle (pbt); characteristic anthropolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…The camera lens was set perpendicularly to the direction of movement of the subjects. The described arrangement of the measurement line was consistent with previous research by the authors of this study [21].…”
Section: Methodssupporting
confidence: 90%
See 4 more Smart Citations
“…The camera lens was set perpendicularly to the direction of movement of the subjects. The described arrangement of the measurement line was consistent with previous research by the authors of this study [21].…”
Section: Methodssupporting
confidence: 90%
“…In this study, the relationship between maximal flexion of the ankle joints (A FLEX ) and the horizontal velocity of swimmers was negative, although the strength of these correlations was different for girls and boys (r = -0,501 and r = -0.206, respectively). The fact that maximising the extension of the ankle joints at the expense of flexion of the ankle joints is an effective strategy in increasing the velocity when performing underwater undulatory swimming was indicated by Wądrzyk et al [21]. This study also showed that the range of motion in the ankle joints did not significantly affect v COM .…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations